The impact of interest rate spreads on the profitability of commercial banks in Ghana; a case study of standard Chartered bank Ghana Limited. - Ameevor, Samuel (2017)
A thesis submitted to the Department of Economics in partial fulfillment of the requirements for award of the degree Master of Science in Economics,